Desenvolvimento de uma máquina de corte CNC de baixo investimento e fácil operação e manutenção - Silva, Felipe Cunha da (2019)
This monography has as it's objective the construction of an CNC Router for small applications, controlled by an Arduino and made of accessible materials, as well as the elaboration of an assemble and operation manual. The machine will be capable of moving simultaneously on X and Y axis and adjust the Z axis depth. It can be operated manually or automatically, by interpreting an g-code (.cnc) previously generated. The manual will embrace general assembling instructions, as well as the installation, setup and operations of the softwares.